Expectativas de equidad y ciudadanía social: Desafíos de legitimación e integración de la democracia chilena. - Martín Tironi; Francisco Carreras (Nuevo mundo - Mundos Nuevos, 2008)
One of the most important challenges of the current democratic order in Chile refers to the need to satisfy the citizenship’s expectations of equity and fairness.  These expectations are fundamentally related with the demand for protection of social rights.  The existing institutional framework has not been able to respond adequately to these expectations as a result of the emphasis that public administration has placed on economic growth and rights associated with free entrepreneurship according to individual efforts and abilities. The political system’s requirement for legitimacy requires, however, an adequate response to these yet unanswered expectations.  Being able to comply and satisfy them not only fosters the material integration of the population, but also contributes to the generation of symbolic mechanisms of social integration, from which subjects can recognize themselves as members of a community of equals.